Modeling, Simulation, and Kinetic Studies of Solvent-Free Biosynthesis of Benzyl Acetate - Vijay Kumar Garlapati; Annapurna Kumari; Paramita Mahapatra; Rintu Banerjee (Journal of Chemistry)
Solvent-free biosynthesis of benzyl acetate through immobilized lipase-mediated transesterification has been modeled and optimized through statistical integrated artificial intelligence approach. A nonlinear response surface model has been successfully developed based on central composite design with transesterification variables, namely, molarity of alcohol, reaction time, temperature, and immobilized lipase amount as input variables and molar conversion (%) as an output variable. Statistical integrated genetic algorithm optimization approach results in an optimized molar conversion of 96.32% with the predicted transesterification variables of 0.47 M alcohol molarity in a reaction time of 13.1 h, at 37.5°C using 13.31 U of immobilized lipase. Immobilized lipase withstands more than 98% relative activity up to 6 recycles and maintains 50% relative activity until 12 recycles. The kinetic constants of benzyl acetate, namely, Km and Vmax were found to be 310 mM and 0.10 mmol h−1 g−1, respectively.